Psycholinguistic and Cultural Implications of German Stimulus Words Humor and Lachen in Association Test - Zubach , Oksana (East European Journal of Psycholinguistics, 2022)
The article is focused on the psycholinguistic and cultural study of individual associative responses to German stimulus words ’Humor’ and ’Lachen’. The goal is to determine individual cognitive activity features in the target ’culture of popular laughter’ (Bakhtin, 1965). The research involved a free word association test aimed to examine the German learners’ perception of the stimulus words. Sixty undergraduate students aged 20-22 of the educational programme "Language and Literature (German). Translation" at Lesya Ukrainka Volyn National University, Ukraine, participated in the word association test. Quantitative analysis of response words, typical and individual responses allowed building semantic gestalt and productive semantic zones that represent the linguistic culture identification features. Nouns, adjectives, and verbs represented productive associations. The analysis of associative fields allowed modelling the interaction of psycholinguistic and lingo-cultural factors for the emergence of responses to the stimulus words ’Lachen’ and ’Humor’. The obtained response words determined communicative, pragmatic, and cognitive productive profiles. Nuclear zones in each associative field tended towards a unified expression of positive emotions. Respondents produced a wide range of semantic potential of stimulus words and frequency of reverse reactions. The expressive spectrum of productivity of individual associations by the respondents is interpretive and results from their cognition of the culture of popular laughter.